(untitled) (The Pakistan Development Review, 2007)
Globalisation has diverse definitions and concepts.1 Globalisation has many facets and has a variety of social, political and economic implications. This term introduced in early 1980, which never precisely defined, is a frequently used word in the political economy. It simply means growing integration of the national economies, openness to trade, financial flows, foreign direct investment and the increasing interaction of people in all facets of their lives. Globalisation also implies internationalisation of production, distribution and marketing of goods and services. International integration implies the adoption of common policies by the individual countries. Between 1870 and 1914, the world was integrated into a single word economy dominated by one power: Great Britain. The government functions were limited and faced many constraints like gold standard and lack of freedom to pursue easy monetary policy. Later governments were burdened by performing many functions like achievement of macroeconomic goals—full employment, economic growth and price stability. Freedom of using macroeconomic policies resulted in greater integration of national economies but at the same time they led to international disintegration and interdependence. Streeten (1998) argues that today global market forces can lead to conflict between states, contributing to international disintegration and weakened governance. Before 1914, the world was more integrated than it is today but it did not prevent the First World War.